N-use efficiency of single, double and synthetic maize lines grown at four N levels in three ecological zones of West Africa - Akintoye, H.A; Kling, J.G; Lucas, E.O (Field crops research, 1999)
Efficiencies in uptake and use of N by maize cultivars have been widely studied, but little has been done on this subject in West Africa. Six single-cross hybrids, three double-cross hybrids and a synthetic line were grown at different N levels (0–210 kg N ha −1) in three ecological zones of West Africa. The maize cultivars differed widely in grain yield and N-accumulation parameters. Most cultivars absorbed similar amounts of N ranging from 2.04 g plant −1 to 2.60 g plant −1, but produced different grain yields, with those that accumulated more N after silking tending to have higher grain yield. Grain yields in the forest zone were lower than those in two Savanna regions. Differences were also observed for N-uptake (total N-uptake per unit N supplied to the soil), N-utilization (grain produced per unit N absorbed from the soil) and N-use efficiency (NUE) (grain produced per unit N supplied to the soil). Cultivars varied in their response to change in available soil N. The hybrids were more efficient in N-use and its component traits than the synthetic cultivar. Hybrid 1368 × KU1414-SR yielded the most grain as well as exhibiting superior traits for N-uptake and N-use efficiency.